2021
DOI: 10.46325/gabj.v5i2.76
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antioxidant effect of the ethanolic extract of Citrullus colocynthis L. plant fruit

Abstract: Citrullus colocynthis L. of the Cucurbitaecea botanical family is a plant widely used in traditional medicine in Algeria. It seems empirically effective in the treatment of various diseases. The aim of the present research is to evaluate the antioxidant and cytotoxic effects, in vitro, of the ethanolic extract of C. colocynthis fruits. The quantitative analysis has shown that the ethanolic extract of C. colocynthis is rich in total polyphenols with a content of 443.62 ± 2.13 µg EAG/mg of extract. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In another study, Rafi et al [108] reported that lycopene may inhibit inflammation in RAW 264.7 cell lines and suggested that fruits that are rich in lycopene could be useful as anti-inflammatory agents. Moreover, protein hydrolysates for watermelon seeds protected RAW 264.7 cells from oxidative damage [109]; while Fetni et al [110] and Darwish et al [111] reported similar effects for fruit extracts of Citrullus colocynthis. Considering the limited reports regarding the anti-inflammatory activity of watermelon fruit, our results could provide useful information about the effect of simple agronomic techniques, such as biostimulant application, on the bioactive properties of fruit extracts.…”
Section: Anti-inflammatory Activitymentioning
confidence: 95%
“…In another study, Rafi et al [108] reported that lycopene may inhibit inflammation in RAW 264.7 cell lines and suggested that fruits that are rich in lycopene could be useful as anti-inflammatory agents. Moreover, protein hydrolysates for watermelon seeds protected RAW 264.7 cells from oxidative damage [109]; while Fetni et al [110] and Darwish et al [111] reported similar effects for fruit extracts of Citrullus colocynthis. Considering the limited reports regarding the anti-inflammatory activity of watermelon fruit, our results could provide useful information about the effect of simple agronomic techniques, such as biostimulant application, on the bioactive properties of fruit extracts.…”
Section: Anti-inflammatory Activitymentioning
confidence: 95%